Pengaruh Suhu Pemanasan terhadap Karakteristik Mutu Minyak Goreng Bekas Pakai Pedagang Gorengan - Agung, Galih S; Rismaya, Rina (Universitas Pattimura, 2024)
Palm cooking oil has been widely used in food processing because it is easily available at a relatively low price in the market. People's habit of repeatedly using cooking oil is considered more economical and can save household costs, but this can be a bad risk to health. This is because repeated use at high temperatures will reduce the quality of cooking oil. This study aimed to determine the effect of heating temperature on the quality of cooking oil used by fried traders in terms of color analysis, free fatty acids, iodine number, and peroxide value. This study used a completely randomized design with heating temperature treatment (150°, 180°, and 210°C) on cooking oil used by fried peddlers, which was repeated two times trial repetition. The results showed that heating temperature significantly increased the redness, free fatty acid content, and peroxide value of used cooking oil. However, the heating temperature significantly reduced the iodine value in used cooking oil. Based on SNI 7709:2019, cooking oil used by fried traders who were given different heating treatments did not meet the quality requirements for cooking oil in term of its free fatty acid content and color quality.